Pregnant women’s knowledge about birth defects and their associated risk factors in Quetta - Omer, Zainab; Syed Jahanzaib; Khan, Rimsha; Mansur, Rida; Naeem, Aqsa; Ahmed, Saboor (Journal of the Pakistan Medical Association, 2026)
Objective: To quantify pregnant women’s knowledge of congenital abnormalities, their associated risk factors and preventative measures, and to determine the association of knowledge level with socio-demographic factors. Method: The multi-centre, cross-sectional study was conducted from October 2023 to March 2024 in Quetta, Pakistan, after approval from the ethics review committee of the Quetta Institute of Medical Sciences, and comprised pregnant women aged at least 18 years who were attending antenatal clinics. Data was collected using a questionnaire. The participants’ knowledge was assessed through 21 close-ended questions. The association of knowledge score with a range of socio-demographic factors was explored. Data was analysed using SPSS 26. Results: Of the 640 mothers, 303(47.3%) were aged 25-34 years, 131(20.5%) had completed secondary school education, 540(84.4%) were housewives, 373(58.3%) were married within their families, and 447(69.8%) lived in urban areas. There were 349(54.5%) participants having moderate knowledge about birth defects, 207(32.3%) had high level of knowledge, and 84(13.1%) had poor knowledge. The knowledge level had significant association with education level (p=0.001) and residence area (p=0.006). Conclusion: Pre-pregnancy counselling shall be made available at antenatal care centres. Maternal obesity and consanguinity shall be pointed out to pregnant women as risk factors for congenital anomalies. Key Words: Congenital abnormalities, Pregnancy, Health knowledge, Attitudes, Practice, Risk factors, Antenatal care, Regression analysis.